BIM-Enabled Design Collaboration for Complex Building - Wang, Jun; Chong, Heap Yih; Shou, W.; Wang, Xiangyu; Guo, J. (Springer, 2014)
Fragmented practices are common in construction industry due to the traditional procurement system and poor adoption of advanced technologies and approaches for construction projects. Building Information Modelling is an emerging technology and able to transform the conventional practice. It can create a collaborative working platform for a project, particularly during the design stage. Therefore, the research aims to improve the conventional design practices by incorporating the BIM technology in addressing the design collaboration for a complex building. A case study was adopted from a complex building in Beijing, China. The data were collected and observed during the design process. A framework was developed to explain the design collaboration process. The findings show the duration of the design has significantly shortened and also improved the design performance in the project. The research renders an important insight into promoting BIM-based design collaboration in the construction industry.